The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1105/tpc.12.6.917
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of Chloroplast FtsH Protein in Tobacco Mosaic Virus–Infected Tobacco Leaves Accelerate the Hypersensitive Reaction

Abstract: In tobacco cultivars resistant to tobacco mosaic virus (TMV), infection results in the death of the infected cells accompanying the formation of necrotic lesions. To identify the genes involved in this hypersensitive reaction, we isolated the cDNA of tobacco DS9, the transcript of which decreases before the appearance of necrotic lesions. The DS9 gene encodes a chloroplastic homolog of bacterial FtsH protein, which serves to maintain quality control of some cytoplasmic and membrane proteins. A large quantity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 65 publications
4
80
0
1
Order By: Relevance
“…Three possibilities should be considered. First, the other homologs may have different functions, as suggested in the case of virus infection in tobacco (Seo et al, 2000). A second possibility is that they are expressed only under certain environmental conditions.…”
Section: The Ftsh Protein Family In Higher Plantsmentioning
confidence: 99%
“…Three possibilities should be considered. First, the other homologs may have different functions, as suggested in the case of virus infection in tobacco (Seo et al, 2000). A second possibility is that they are expressed only under certain environmental conditions.…”
Section: The Ftsh Protein Family In Higher Plantsmentioning
confidence: 99%
“…The function and location of some members of the FtsH-p1 and FtsH-p2 groups have recently been reported. In Arabidopsis, the proteins from these groups are located in the thylakoid membrane and are apparently involved in the light-induced turnover of the Photosystem II D1 protein (FtsH-p1) and thylakoid membrane biogenesis (FtsH-p2) (Lindahl et al, 2000;Chen et al, 2000), while tobacco FtsH-p1 has been associated with the hypersensitive reaction (Seo et al, 2000). The data shown in Table II and Figure 3 indicates that sugarcane EST clusters present high similarity with these proteins.…”
Section: Resultsmentioning
confidence: 96%
“…A second type of thylakoidal FtsH-like protein has been found in tobacco, where it is related to a hypersensitivity response, and in Arabidopsis where it is involved in the light-induced turnover of the Photosystem II D1 protein (Seo et al, 2000;Lindahl et al, 2000). In pea cells, a thylakoid membrane metalloprotease stimulated by zinc ions has been described as being responsible for the degradation of unassembled subunits of the cytochrome b 6 f complex (Ostersetzer and Adam, 1997), this protein might be either an already described FtsH-like protein or a new type of AAA metalloprotease.…”
Section: Introductionmentioning
confidence: 99%
“…9). In addition, it has previously been shown that a chloroplast-specific FtsH protease is destabilized during N-mediated resistance against TMV (Seo et al, 2000) and light is required for the timely activation of the HR by N (Chandra-Shekara et al, 2006). Thus, we hypothesize that THF1 inhibits cell death by preventing light-induced damage in the chloroplasts and that inhibition of THF1 accumulation would in turn accelerate the negative effects of such damage, thus promoting cell death.…”
Section: A Potential Role For Thf1 In the Regulation Of Plant Cell Deathmentioning
confidence: 87%